The Effects of Health Insurance Parity Laws for Substance Use Disorder Treatment on Traffic Fatalities: Evidence of Unintended Benefits - Ioana Popovici; J. Catherine Maclean; Michael French (Institute of Labor Economics (IZA), 2017)
Each year, 10,000 individuals die in alcohol-impaired traffic accidents in the United States, while psychoactive drugs are involved in 20% of all fatal traffic accidents. We investigate whether state parity laws for substance use disorder (SUD) treatment have the unintended benefit of reducing fatal traffic accidents. Parity laws compel insurers to cover SUD treatment in private insurance markets, thereby reducing the financial costs of and increasing access to treatment for beneficiaries. We employ over 20 years of administrative data from the national Fatal Accident Reporting System coupled with a differences-in-differences research design to investigate the potential spillover effects of parity laws to traffic safety. Our findings indicate that passage of a state parity law reduces fatal traffic accident rates by 4.1 to 5.4%. These findings suggest that government regulations requiring insurers to cover SUD treatment can significantly improve traffic safety, possibly by reducing the number of impaired drivers on roadways.
Keywords: I1; I13; I18; 330; traffic fatalities; substance use disorder (SUD) treatment; traffic safety; health insurance parity laws